2019
DOI: 10.1111/1756-185x.13764
|View full text |Cite
|
Sign up to set email alerts
|

Adipose‐derived stromal/stem cells successfully attenuate the fibrosis of scleroderma mouse models

Abstract: Aim Systemic sclerosis (SSc) is an autoimmune disease characterized by skin and lung fibrosis. Although SSc has a high mortality risk, an effective treatment for the disease has not been established yet. Mesenchymal stromal/stem cells (MSCs) are multipotential nonhematopoietic progenitor cells that have the ability to regulate immune responses. Adipose‐derived stromal/stem cells (ASCs), one of the types of MSCs, have the advantage of accessibility and potent immunomodulatory effects when compared with other MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Fibrosis is one of the major factors that inhibit lymphatic regeneration [4]. ADSC transplantation appears effective against fibrosis because ADSCs and their secreted factors activate dermal fibroblasts and suppress inflammatory cells [26,38]. ADSC transplantation should also be effective against lymphorrhea, promoting lymphatic regeneration and surrounding tissue normalization.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosis is one of the major factors that inhibit lymphatic regeneration [4]. ADSC transplantation appears effective against fibrosis because ADSCs and their secreted factors activate dermal fibroblasts and suppress inflammatory cells [26,38]. ADSC transplantation should also be effective against lymphorrhea, promoting lymphatic regeneration and surrounding tissue normalization.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies demonstrated that ASC administration was sufficient to attenuate BLM-induced scleroderma by suppressing the infiltration of CD4 + and CD8 + T cells and macrophages into the dermis, but it also reduced the frequency of CD4 + T cells and effector B cells in the spleens of SS mice [247]. Moreover, there was a decrease in mRNA expression of Col1a2 and profibrotic cytokines such as IL-6 and IL-13, suggesting an immunomodulatory and anti-inflammatory effect of ASCs in fibrotic skin [247].…”
Section: Skin Fibrosismentioning
confidence: 97%
“…Given that fibrotic skin diseases are complex, chronic, and heterogeneous and the evaluation of therapy is difficult, effective treatments have not been established so far. Nevertheless, among potential systemic antifibrotic therapies under investigation, those that employ MSCs have emerged as among the most promising [244][245][246][247][248].…”
Section: Skin Fibrosismentioning
confidence: 99%
“…ADSCs were found to stimulate the polarization of macrophages into the M2 phenotype by secreting IL-6 in the in ammatory environment of peritoneal brosis [20], or by activating the PI3K/STAT3-dependent pathway in cardiac brosis [21]. They were also reported to suppress the in ltration of macrophages and T cells into the injured side in a bleomycin-induced scleroderma model [22], prevent leucocyte in ltration and modulate the expression of IL-1b, TNF-a, IL-6 in a combined model of peritoneal brosis and chronic kidney disease [23]. Additionally, ADSCs increased the number of type II alveolar epithelial cells in a radiation-induced lung brosis model [24], and ameliorated radiation-induced brosis by secreting HGF to downregulating the expression of TGFβ, CTGF, IL-1, TNF and NF-κB, as well as recruiting BMSCs to the injured site [25].…”
Section: Introductionmentioning
confidence: 99%